Disorientasi Seksual Sebagai Alasan Fasakh Perkawinan (Analisis Putusan No.300/Pdt.G/Pa.Pyb) - Betawi, Usman (Fakultas Syariah dan Hukum, 2024)
Abstract: The research analyzes a court decision regarding the annulment of a marriage filed by a wife due to her husband, who is a homosexual, concealing his sexual orientation before marriage. The study delves into legal perspectives and Islamic Family Law (KHI) regarding marriage annulment due to sexual disorientation, judicial considerations in the decision, and the validity analysis of sexual disorientation as a ground for marriage annulment (fasakh). This research employs a juridical-normative approach with a qualitative method. The study reveals that Indonesia lacks a specific law governing the annulment of marriage due to sexual disorientation. However, drawing upon Article 72 (2) of the Compilation of Islamic Law (Kompilasi Hukum Islam) and the principle of